ANALISIS KUALITATIF SENYAWA PARASETAMOL (ACETAMINOPHEN) PADA URIN DAN RAMBUT MENGGUNAKAN KROMATOGRAFI GAS – SPEKTROMETRI MASSA (GC-MS) - Komang Ari Gunapria Darmapatni; A. A. Bawa Putra; Ni K. Ariati; Ni M. Suaniti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
Paracetamol (acetaminophen) is one of analgesic-antipyretic drugs which can be commercially obtained. The research aimis to analyze qualitatively the presence of paracetamol (acetaminophen) in urine and human hair by gas chromatography-mass spectrometry (GC-MS). Urine and human hair sample were obtained from patients (volunteers) who consume paracetamol in therapeutic dose without consumption patterns change. Extraction of paracetamol in urine used ethyl acetate and in human hair used methanol. The extract was then derivatized with BSTFA and 1% TMCS and analyzed using gas chromatography-mass spectrometry (GC-MS). The result showed that urine samples after 1, 2, and 3 hours consuming paracetamol contained acetaminophen-TMS. Those after 24, 168, and 720 hours after consuming paracetamol did not contain acetaminophen-TMS. In human hair, the acetaminophen-TMS was found in samples of 1, 2, 3, 24, 168, and 720 hours after consuming paracetamol.